2019
DOI: 10.1177/0886260519869078
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and Loneliness in Peer-Victimized Adolescents

Abstract: The purpose of the present study was to analyze the relationships between forgiveness, motivations for revenge, avoidance, and benevolence; loneliness, emotional loneliness and positive subjective evaluation of the social network; and peer victimization in schools, relational, overt physical, and overt verbal, based on gender. A battery of instruments was administered to 617 Spanish students (50.7% boys and 49.3% girls), aged between 10 and 16 years ( M = 13.04 years, SD = 1.80 years) from primary and secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 60 publications
3
4
0
1
Order By: Relevance
“…Findings showed that, as predicted, non-involved adolescents perceived the highest levels of both mother and father implication and acceptance than aggressors and A-V, who presented the lowest levels of mother and father involvement. These results are in line with those of previous studies [13,17,18,62] and highlight the relevance of warmth and affective responsiveness in childhood and early adolescence to reduce the risk of psychosocial maladjustment and adolescents' peer aggression [16,30,31]. In addition, prior studies have concluded that both indulgent and authoritative parenting styles are the most protective against peer aggression and cyberbullying [14,17,22,53,63].…”
Section: Discussionsupporting
confidence: 91%
“…Findings showed that, as predicted, non-involved adolescents perceived the highest levels of both mother and father implication and acceptance than aggressors and A-V, who presented the lowest levels of mother and father involvement. These results are in line with those of previous studies [13,17,18,62] and highlight the relevance of warmth and affective responsiveness in childhood and early adolescence to reduce the risk of psychosocial maladjustment and adolescents' peer aggression [16,30,31]. In addition, prior studies have concluded that both indulgent and authoritative parenting styles are the most protective against peer aggression and cyberbullying [14,17,22,53,63].…”
Section: Discussionsupporting
confidence: 91%
“…The current model indicates forgiveness is associated with the cognitive discrepancy model of loneliness, in that a tendency to forgive correlates with perceived relational closeness and support. These results enhance recent research emphasizing the negative association between forgiveness and loneliness (Leon-Moreno et al, 2019). Forgiveness is defined as a predisposition involving cognitive, emotional, and behavioral processes whereby an individual replaces negative thoughts, behaviors, and emotions, such as anger, hostility, avoidance, and distrust, for more adaptive, positive emotions and cognitions, such as empathy and compassion (Quintana-Orts & Rey, 2018).…”
Section: Discussionsupporting
confidence: 85%
“…In previous studies, it has been observed that boys are more likely than girls to engage in various forms of direct aggression, actions directly targeted at the victim (e.g., physical violence or sending harmful messages and images without the need to conceal identity) [ 32 , 60 ]. However, girls are more likely than boys to carry out various forms of indirect aggression, actions that allow the aggressor to hide his or her identity from the victim, sometimes even making it difficult for the victim to know that he or she has been the object of any intentional harm [ 61 , 62 ]. These actions include spreading rumors or telling others not to associate with the victim.…”
Section: Discussionmentioning
confidence: 99%